Exploring Variation in the Strength of Association of a Validated Recidivism Risk Score With Seven Common Measures of Juvenile Recidivism: A Research Note - Siennick, Sonja E. (Youth violence and juvenile justice, 2023)
The purpose of this study was to compare the predictive strength of a previously validated risk score across seven different operationalizations of juvenile recidivism. Drawing on data from the Florida portion of the Measuring Juvenile Reoffending Study, the study examines two research questions. First, do recidivism risk scores significantly predict a variety of measures of juvenile recidivism? And second, do risk scores exert statistically different effects on different measures of juvenile recidivism? The findings revealed that risk score significantly predicted all seven measures of juvenile recidivism. In addition, the only evidence of statistically different associations across measures of recidivism came from marker event (i.e., types of system contact) comparisons. Total risk score was a significantly stronger predictor of referral than of adjudication/conviction and a stronger predictor of adjudication and commitment. Altogether, our results highlight the importance of validating risk assessment scores on multiple different operationalizations of juvenile recidivism.